2016
DOI: 10.1016/j.chemosphere.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Review of OPFRs in animals and humans: Absorption, bioaccumulation, metabolism, and internal exposure research

Abstract: h i g h l i g h t sThe absorption, bioaccumulation, metabolism and internal exposure of OPFRs are reviewed. Inhalation, ingestion and dermal contact are the main OPFRs absorptionpathways for humans. General in vivo and in vitro metabolic pathways of three different types of OPFRs are proposed. DAPs and MAPs are considered as putative biomarkers for the assessment of internal exposure of OPFRs in humans. a r t i c l e i n f o t r a c tDue to their widespread use, organophosphate flame retardants (OPFRs) are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
225
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 443 publications
(229 citation statements)
references
References 90 publications
3
225
1
Order By: Relevance
“…Although the half-life of TPHP in the human body is unknown, it is thought to be metabolized and excreted rapidly from the body, which may cause high intra-individual variability in spot urine measures (Aylward et al 2014; Hou et al 2016; Muir et al 1983). We found markedly lower ICCs over our one-year study period compared to previous studies that reported moderate to strong reliability over much shorter time periods (ICC range: 0.35 to 0.7; see Table S4) (Cequier et al 2015; Hoffman et al 2014, 2015b; Meeker et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the half-life of TPHP in the human body is unknown, it is thought to be metabolized and excreted rapidly from the body, which may cause high intra-individual variability in spot urine measures (Aylward et al 2014; Hou et al 2016; Muir et al 1983). We found markedly lower ICCs over our one-year study period compared to previous studies that reported moderate to strong reliability over much shorter time periods (ICC range: 0.35 to 0.7; see Table S4) (Cequier et al 2015; Hoffman et al 2014, 2015b; Meeker et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Humans may be exposed to TPHP through inhalation, ingestion of indoor dust, and dermal absorption through contact with dust, source materials, or direct partitioning from vapor (Pillai et al 2014). The half-life of TPHP in humans is unknown, but is thought to be on the order of hours to days (Hou et al 2016). However, because of its widespread use and ubiquity in the indoor environment, exposures may be relatively constant over time.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their ubiquitous presence in the environment, accumulation potential, and toxic effects, PBDEs have gradually been banned/ restricted and replaced by alternative flame retardants. However, several studies have demonstrated that chlorinated OPs have more adverse effects and are much more persistent than PBDEs [1,4]. The OPs are a group of derivatives of phosphoric acid that exhibit excellent flame retardancy and flexibility, and they are widely used as flame retardants and/or plasticizers in a range of products, such as electronic/electric equipment, furniture and decorative materials, building materials, textiles, and packing.…”
Section: Introductionmentioning
confidence: 99%
“…With the ban/restriction on PBDEs, the production and application of OPs has increased sharply [1,3], resulting in elevated levels in the environment. However, several studies have demonstrated that chlorinated OPs have more adverse effects and are much more persistent than PBDEs [1,4]. In recent years, the occurrence, distribution, and toxicity of OPs has been a subject of increasing concern in the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…The low-dose concentrations of TCEP and TCIPP used in our study correspond to a 2.9-and 35.7-fold higher compared to the maximal concentrations found in human serum respectively. However, based on dust ingestion, which is a major route of exposure for humans to FRs (Hou, Xu, & Wang, 2016), it was estimated that toddlers were exposed to higher levels of TCEP and TCIPP compared to adults by a factor of 10 or more (Van den Eede, Dirtu, Neels, & Covaci, 2011), indicating that the concentrations used in our study may hold relevance to human health by being potentially physiologically relevant.…”
Section: Discussionmentioning
confidence: 91%